BERMAIN DAN BELAJAR BAHASA INGGRIS BERBASIS PENDIDIKAN KARAKTER - Samuel Gunawan; Jenny M. Djundjung; , Meilinda (SHARE: Journal of Service Learning, 2013)
The Community Service Project funded by the Higher Education IbM grant entitled "English Communication Competence for Character Development in the Children Study Group in Kelurahan Dr Soetomo, Surabaya", was carried out in September and October 2013. The project aimed at helping to uplift the region to be a participating region in support of Surabaya as a child-friendly and decent city. In implementation, the project has been attended by no less than 50 foster children of the local Early Childhood Education (ECE), RW 3, 6 lecturers, 16 students, and 8 local ECE attendants. The project has contributed some results, such as: materials for developing English communication competence in support of character development; institutional strengthening of the local ECE, RW 3, Kelurahan Dr. Soetomo, Surabaya; empowering the competence of the local ECE attendants; facilitating playing and learning activities for the development of English communication competence for character development at the local ECE; demonstrations of English communication competence based on character development. Finally, the project has contributed the strengthening and empowering of the human resources, and provided some insight to those who have directly and indirectly participated in the project.